Hubungan Karakteristik Sosiodemografi Terhadap Pendapatan Usahatani Lada Di Kabupaten Bengkayang - Alberto, Japo; Suyatno, Adi; Kusrini, Novira (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
The income of pepper farming is significantly influenced by various aspects, including sociodemographic factors. This study aims to analyze the relationship between sociodemographic characteristics and pepper farming income in Bengkayang Regency. The collected data were processed and analyzed using the Spearman Rank correlation test. The results of the study indicate that sociodemographic characteristics such as education level, experience, and land area have a significant relationship with pepper farming income in Bengkayang Regency, with land area being the most dominant factor. On the other hand, age and gender did not show a significant influence.